تقويم أسئلة الأدب والنصوص في الشهادة الدينية العالية الماليزية في ضوء مستويات بلوم المعرفية: دراسة وصفية = Evaluation on the questions of al-adab wa al-nusus in Malaysian high religious education certificate (STAM) in the light of Bloom’s Taxonomy: a descriptive study = Penilaian soalan al-adab wa al-nusus dalam Sijil Tinggi Agama Malaysia (STAM) berdasarkan tahap pengetahuan Bloom: satu kajian deskriptif - Ismail, Taufik; Raslan, Abdul Ghafur; Sahrir, Muhammad Sabri (IIUM Press, International Islamic University Malaysia, 2020)
The evaluation is indispensable in the teaching and learning processes, and it should be assigned to everyone who bears the name of “teacher” wherever his/her service is, in order to identify the extent of his/her success in achieving the goals that he/she seeks from his teaching work, and to discover the state of the mental skills of learners with weakness and strength, so that he/she can address weaknesses and stabilize strengths, in addition to improving and developing them. Hence, the study aims to analyze the Arabic language exam questions of the Malaysian High Religious Education Certificate between 2013-2015 in the light of Bloom's taxonomy (remembering, understanding, applying, analyzing, evaluating, and creating). The study adopted the descriptive analytical method, and used frequency and percentages: to consider 110 paragraphs, i.e. the sum of the questions of the Arabic language exams for Malaysian High Religious Education Certificate. The most prominent results are that the focus on the level of remembrance was high, and its repetitions is (58) by (53%), then the level of comprehension’s frequency is (41) by (37%). Whereas, the level of application, its frequency is (7), at the rate of (6%), and the levels of analysis and evaluation are of frequency (1.3) with two percentages (3% and 1%), respectively. As for the level of creativity, it has no position in the total of questions. **************************************************************************** Penilaian adalah sangat diperlukan dalam proses pengajaran dan pembelajaran, dan semua yang bergelar "guru" di mana sahaja perkhidmatannya, ingin mengetahui sejauh mana kejayaannya dalam mendidik, dan ingin mengetahui sejauh mana kefahaman para pelajar agar dapat mengatasi kelemahan dan memantapkan kekuatan, selain memperbaiki dan mengembangkannya. Sehubungan itu, objektif kajian ini adalah bertujuan untuk menganalisis soalan peperiksaan Bahasa Arab dalam Sijil Tinggi Agama Malaysia (STAM) pada tahun 2013-2015 menurut taksonomi domain kognitif Bloom (mengingat, memahami, menerapkan, menganalisis, menilai, dan mencipta). Kajian ini menggunakan pendekatan analisis kandungan sebagai unit analisis untuk menganalisis soalan. Jumlah soalan adalah 110. Hasilnya menunjukkan bahawa soalan peperiksaan Bahasa Arab untuk Sijil Tinggi Agama Malaysia pada tahun-tahun yang disebut dalam kajian ini memfokuskan pada kemahiran berfikir peringkat rendah (mengingat 53%, memahami 37%, menerapkan 6%). Sebaliknya, menganalisis berlaku dalam kemahiran berfikir yang lebih tinggi (3%), sementara dua tahap yang lain, menilai dan membuat mendapat perhatian yang rendah masing-masing pada 1% dan 0%.